Global Analysis of Breast Feeding and Risk of Symptoms of Asthma, Rhinoconjunctivitis and Eczema in 6-7 Year Old Children: Isaac Phase Three - Mallol-Villablanca, E (Elsevier Doyma, 2011)
Background: In Phase Three of the International Study of Asthma and Allergies in Childhood (ISAAC), we investigated the relationship between breast feeding in infancy and symptoms of asthma, rhinoconjunctivitis and eczema in 6-7 year old children. Methods: Parents or guardians of 6-7 year old children completed written questionnaires on current symptoms of asthma, rhinoconjunctivitis and eczema, and on a range of possible asthma risk factors including a history of breast feeding ever. Prevalence odds ratios were estimated using logistic regression, adjusted for gender, region of the world, language, per capita gross national income, and other risk factors. Results: In all 206,453 children from 72 centres in 31 countries participated in the study. Reported breast feeding ever was not associated with current wheeze, with an odds ratio (adjusted for gender, region of the world, language, per capita gross national income, and factors encountered in infancy) of 0.99 (95% CI 0.92-1.05), current rhinoconjunctivitis (OR 1.00, 95% CI 0.93-1.08), current eczema (OR 1.05, 95% CI 0.97-1.12), or symptoms of severe asthma (OR 0.95, 95% CI 0.87-1.05). Breast feeding was however associated with a reduced risk of severe rhinoconjunctivitis (OR 0.74, 95% CI 0.59-0.94) and severe eczema (OR 0.79, 95% CI 0.66-0.95). Conclusions: There was no consistent association between breast feeding use in the first year of life and either a history or current symptoms of wheezing, rhinoconjunctivitis or eczema in 6-7 year old children, but possibly an effect on severe symptoms of the latter two conditions. © 2011 SEICAP.